2022
DOI: 10.3389/fgene.2022.816123
|View full text |Cite
|
Sign up to set email alerts
|

Complete Chloroplast Genomes and Comparative Analyses of Three Ornamental Impatiens Species

Abstract: Impatiens L., the largest genus in the family Balsaminaceae with approximately 1,000 species, is a controversial genus. Due to the conflict of morphological features and insufficient genomic resources, the studies of systematic evolution and understanding of taxonomic identification are considered to be very limited. Hence, we have sequenced the complete chloroplast genomes of three ornamental species (Impatiens balsamina, I. hawkeri, and I. walleriana), and compared them with previously published wild species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 56 publications
1
9
1
Order By: Relevance
“…Analysis of oligonucleotide repeat in seven cp genomes indicated that the number and length of repeat sequences differed among genomes and were distributed randomly, with repeat sequences ranging from 30 to 82 bp and most being within 30 -46 bp (Figure 4B). Meanwhile, 274 long repeats were identified, including 149 P repeats, 124 F repeats, and 1 R repeat, with P and F being more than R and C, a pattern consistent with most plastid genomes of angiosperms (Vu et al, 2020;Luo et al, 2022). R repeats were only present in A. campylantha, while C repeats were absent in all seven Ajuga species (Figure 4A).…”
Section: Repeat Sequencessupporting
confidence: 62%
“…Analysis of oligonucleotide repeat in seven cp genomes indicated that the number and length of repeat sequences differed among genomes and were distributed randomly, with repeat sequences ranging from 30 to 82 bp and most being within 30 -46 bp (Figure 4B). Meanwhile, 274 long repeats were identified, including 149 P repeats, 124 F repeats, and 1 R repeat, with P and F being more than R and C, a pattern consistent with most plastid genomes of angiosperms (Vu et al, 2020;Luo et al, 2022). R repeats were only present in A. campylantha, while C repeats were absent in all seven Ajuga species (Figure 4A).…”
Section: Repeat Sequencessupporting
confidence: 62%
“…There are more than 1,000 species of Impatiens in the world ( Luo et al., 2022 ). Studies on their evolution and taxonomy show that the number of sepals is one of the signs of evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Impatiens is rich in germplasm resources, and there are approximately 120 species in the Yunnan-Guizhou Plateau (Luo et al, 2022). In this study of some areas of Yunnan and Guizhou, 48 species of Impatiens were collected, which is, of course, only a fraction of the local species.…”
Section: Impatiens Germplasm Resourcesmentioning
confidence: 94%
“…There are two genera of the Balsaminaceae, and one is Impatiens. This genus is rich in germplasm resources, with more than 1 000 species in the world and more than 260 species in China (Luo et al, 2022). However, the classification of Impatiens is very challenging Hai-hao He 1 , Ming-lan Ma 1 , Xin-yi Chen 1 , Xin-yi Li 1 , Fan Li 1 , Qiu-yan Zhao 1 , Xiao-shuai He 1 , Yi Tan 1 , Su-ping Qu 2 , Hai-quan Huang 1, *, Mei-juan Huang 1, * because it is difficult to make and preserve specimens (Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation